Engaging the Intersections of Equity and Technology in Teacher Education Instruction, Curriculum and Pedagogies - Baroud, Jamilee (Université d'Ottawa / University of Ottawa, 2020)
This study examined the critical digital practices and pedagogies of two professors from two different Canadian provinces – Ontario and British Columbia. Employing a qualitative multi-site case study methodology and a tri-theoretical framework that I refer to as a Critical Intersectional Technological Integration framework (CITI), I investigated the meaning of digital and critical literacy within mandatory educational texts such as provincial curriculum documents and syllabus statements. I engage with how educators mobilized these texts to become critical digital literacy learners, producers, and communicators of knowledge. This study provides a detailed analysis of how two professors understand their pedagogical conceptualizations and enactments of critical digital pedagogies and lessons learned in regard to future pedagogy and practice. Several significant findings emerged from this research study. First, the two professors’ teaching and schooling experiences revealed how intertwined equity and diversity issues were, which influenced their pedagogies and practices as critical digital literacy teacher educators. Second, the critical digital literacy teacher educators modelled expansive definitions of literacy to include the consumption, critique, and creation of digital content. Third, deliberately exploring issues of diversity and equity was a strategy employed by the professors to support teacher candidates to appreciate the complexity of education and arrive at the understanding that schooling, pedagogy, and curriculum are not neutral practices. I argue that this work should not be left solely to teacher educators; rather, teacher preparation programs must play a larger role in preparing and supporting teacher educators with both the technical and pedagogical know-how of meaningfully designing and integrating critical digital practices into their courses.
Keywords: Critical digital literacies; Intersectionality; Teacher education; Equity